Pengaruh Variasi Bentuk Potongan Agregat Bambu Petung Terhadap Berat Jenis dan Kuat Tekan Beton Ringan - Yoga Putra Darmansyah; Farlin Rosyad (Sekolah Tinggi Teknik - PLN, 2019)
The use of bamboo as an aggregate substitution is an effort to reduce the specific gravity of concrete, especially in the production of lightweight concrete. The use of bamboo material has the consequence of decreasing the compressive strength value of concrete. This study aims to determine the magnitude of the effect of the use of bamboo substitution on concrete on the compressive strength and specific gravity values. The bamboo material used is sized 15-30 mm in various shapes. The type of bamboo used is petung bamboo (Dendrocalamus Asper). As for the variations in the use of bamboo in the test specimens are 50% and 75% pieces of bamboo of the same shape, 50% and 75% pieces of bamboo form variations, of the weight of coarse aggregate. The research sample is in the form of a cube test object with a size of 15 cm x 15 cm x 15 cm. Based on the results of the study there was a decrease in the value of the concrete mortar slump along with the addition of the percentage of bamboo aggregate substitution. Concrete absorbs water which is indicated by an increase in water absorption in concrete test specimens which reaches 4.81%. The decrease also occurs in the specific gravity and compressive strength of the test specimen. The minimum value of average concrete density with bamboo substitution for various variations was obtained at 1902.2 kg/m3 (Bamboo Test Objects with Variation Shape 75%), and a maximum of 1991.1 kg/m3 (Bamboo Test Objects with 50% Equal Shape and Objects Bamboo Test Variation in the Form of 50%). The maximum compressive strength value is 135.1 kg/cm2 (Bamboo Test Objects of the Same Shape of 50%) and a minimum of 104.4 kg/cm2 (Bamboo Test Objects of 75% Variation Shape). Variations in the shape of bamboo pieces do not have much effect on the compressive strength of concrete.